ANALYSIS OF GROWTH OPPORTUNITY, NET WORKING CAPITAL, LEVERAGE, AND CASH CONVERSION CYCLE INFLUENCE ON CASH HOLDINGS OF COMPANIES FROM FOOD AND DRINK SUB SECTOR IN INDONESIA STOCK EXCHANGE - I Gede Wiradharma; Herlina Pusparini; Nina Karina Karim (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2017)
The objective of this study is to analyze and determine the influence of growth opportunities, net working capital, leverage, and cash conversion cycle on cash holdings of food and beverage companies listed in Indonesia Stock Exchange. The population in this study is the entire manufacturing companies from food and beverage sub sectors listed in Indonesia Stock Exchange during 2010-2013. The samples in this study were 19 companies that were obtained based on purposive sampling method. Hypotheses testing based on multiple linear regression show that: (1) growth opportunity has no significant or positive influence on corporate cash holdings; (2) net working capital has significant and positive influence on corporate cash holdings; (3) leverage has no significant or positive influence on cash holdings company; (4) cash conversion cycle has no significant or negative effect on corporate cash holdings.